Rising Caesarean Section Rates in Bani Walid: Incidence and Underlying Causes - Zohra S. Algadhi (African Journal of Advanced Pure and Applied Sciences, 2025)
The global rise in cesarean deliveries (CDs) has become a significant public health concern due to its implications on maternal and neonatal outcomes, healthcare costs, and resource utilization. This paper explores the causes and incidence trends of cesarean deliveries and reviews common medical and non-medical indications. A cross-sectional study was conducted from 2018 to 2023 at Bani Walid General Hospital, where data were collected from a hundred randomly selected pregnant women using a structured, self-developed questionnaire. The questionnaire included demographic data and questions related to obstetric history and health conditions influencing delivery mode. Data analysis was performed using Microsoft Excel. This research seeks to provide valuable insights into the factors influencing surgical deliveries in this region.